Input use under cost‐of‐production crop insurance: Theory and evidence. (28th March 2020) - He, Juan; Zheng, Xiaoyong; Rejesus, Roderick; Yorobe, Jose
Abstract: There have been a number of previous studies that examined the effects of yield‐ or revenue‐based crop insurance products on input use of farmers. However, no study has specifically investigated the input use impacts of a cost‐of‐production (COP) crop insurance policy, even though this type of crop insurance is the predominant one used in several other countries outside of the United States (such as the Philippines and China). This article aims to theoretically and empirically examine the effect of a COP crop insurance product on farmers' chemical input use. Our theoretical model suggests that the effect of COP insurance on input use can either be positive or negative, with the resulting impact depending on the strengths of (a) the traditional moral hazard effect of insurance (i.e., an input use decreasing effect); versus (b) the marginal incentives to apply more inputs due to input levels being the main determinant for expected indemnity amounts in this type of insurance (i.e., an input use increasing effect). A survey data set from corn farmers in the Philippines is then used to empirically illustrate how a particular COP insurance product influences input use in a real‐life context. In this case, we find that COP insurance increases the use of chemical inputs (e.g., fertilizers and total chemical expenditure), implying that the positive marginal incentive to apply more inputs dominates the negative moral hazard effect.